2011
DOI: 10.1007/s00339-010-6172-4
|View full text |Cite
|
Sign up to set email alerts
|

Zone plate focused soft X-ray lithography

Abstract: The zone plate focused soft X-rays of a scanning transmission X-ray microscope have been used to pattern poly(methyl methacrylate) and poly(dimethylglutarimide) films by a direct write method which is analogous to lithography with a focused electron beam. The lithographic characteristics of both polymers have been determined for 300 eV X-rays. With low doses (1 MGy), developed lines 40 ± 5 nm wide were created in poly(methyl methacrylate). At higher doses an exposure spreading phenomenon substantially increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Both prior methods extrapolate the full PSF from data in only one direction, and assume that the PSF is radially symmetric. However, we have shown that this assumption is not always true, 17 and it is certainly not the case for each of the three STXM systems we have investigated. Knife edge measurements are also commonly radially extrapolated.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Both prior methods extrapolate the full PSF from data in only one direction, and assume that the PSF is radially symmetric. However, we have shown that this assumption is not always true, 17 and it is certainly not the case for each of the three STXM systems we have investigated. Knife edge measurements are also commonly radially extrapolated.…”
Section: Discussionmentioning
confidence: 79%
“…We have previously determined that PMMA is fully removed from the substrate if it receives a dose of 1 MGy, but even a dose of 0.1 MGy will result in partial removal of material. 17 The developed films are then read out using an atomic force microscope (AFM). Here, we explore more fully the relationship between developed pattern features, properties of the ZP, and its illumination.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Details of the pattern generation program and the calculation of doses, which are believed to be precise within 10%, have been reported previously. 3,7,8 16 The performance of both developer/resist systems for this application has been explored previously. 3 To develop, a sample was held with locking tweezers, then fully immersed in a vial containing the PMGI developer solution and gently stirred for 10 s. The sample was then immediately immersed into a waiting vial containing the PMMA developer solution and stirred for 30 s. Afterward, the sample was allowed to dry in ambient air.…”
Section: Scanning Transmission X-ray Microscope (Stxm)mentioning
confidence: 99%
“…Caster et al 2 using hydrogen silsesquioxane (HSQ) as the resist, were able to achieve 90 ± 14 nm lines. Recently Leontowich et al, 3 working at 300 eV and much lower X-ray exposures, were able to achieve 40 ± 5 nm lines in PMMA. The demonstrated feature size here was quite close to the Rayleigh resolution limit dictated by the properties of the zone plate lens used.…”
Section: Introductionmentioning
confidence: 97%
“…Electron beam lithography (EBL) 9,10 and focused ion beam lithography (FIB) 11,12 have a resolution as high as few nanometers; however, they are time-consuming and expensive. Deep-UV or X-ray lithography, 13,14 interferometric lithography (IL), 15 and nanoimprint lithography (NIL) 16 are cost less and are more productive than EBL and FIB; however, these methods highly depend on the expensive masks. Combining with the lithography methods mentioned above, etching and deposition techniques are applied to do the post processes to transfer the nano-patterns to silicon wafers or glass surfaces.…”
Section: Introductionmentioning
confidence: 99%